ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN, DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Fitri Defiana, Setyaningsih Sri Utami & Retno Susanti (Universitas Slamet Riyadi, 2017)
This study aims to analyze (1) the effect of service quality on customersatisfaction; (2) The impact of service quality on customer loyalty; (3) the effect ofcustomer satisfaction on customer loyalty; (4) the effect of service quality and customerloyalty mediated by customer satisfaction. The study population was all subscribersCopy, Stationery and Toll EN Mandiri Alastuwo Kebakkramat with a sample of 100respondents. Data collection technique used questionnaire through the stages of testingthe validity and reliability test. Terms regression using classic assumption test. Datawere analyzed using path analysis. The conclusion of each hypothesis test results showthat, the quality of service a significant effect on customer satisfaction, service qualitysignificantly influence customer loyalty, customer satisfaction significantly influencecustomer loyalty, customer satisfaction mediates the impact of service quality oncustomer loyalty. The conclusion from these results that the entire hypothesis can beaccepted and proven true.Keywords: service quality, customer satisfaction, loyalty